The Deformation Mechanisms in Process of Crack Propagation for Alpha Titanium with Compounding Microdefects - Ying Sheng; Xiang-guo Zeng (Advances in Materials Science and Engineering)
The multiscale analysis method based on traction-separation law (TSL) and cohesive zone law was used to describe the cross-scale defective process of alpha titanium (α-Ti) material with compounding microdefects in this paper. First, the properties of T-S curve and the reasonable range of T-S area relative to the length of defects were discussed. Next, based on the conclusions above, the molecule dynamics analysis of three models of α-Ti with compounding microdefects was conducted and cross-scaly simulated. The phenomenon, principles, and mechanisms of different compound microscale defects propagation of α-Ti were observed and explained at atomic scale, and the effects of different microdefects on macrofracture parameters of materials were studied.